Digital Piety and Religious Identity in Indonesian Gen Z: A Critical Discourse Analysis of Islamic Memes on Instagram - Indrawan, Fani; Faizi, Ahmad; Eviana, Eva; Riantiningrum, Regina (Bilingua, 2026)
This study examines how Islamic-themed memes on Instagram represent the social reality and religious identity of Indonesian Gen Z through humor and digital discourse. The data is five purposively selected memes, categorized into five thematic dimensions: behavior and social control, intellect and belief, discipline and character, psychology and life solutions, and lifestyle and consumption. The analysis is using Fairclough’s Critical Discourse Analysis (CDA) to identify three dimensions of textual analysis, discursive practice, and socio-cultural practice. The findings reveal that Islamic memes function not merely as entertainment, but as discursive tools for negotiating religiosity within contemporary digital culture. At the textual level, the memes employ irony, linguistic inversion, symbolism, and visual juxtaposition to communicate moral and theological messages in relatable ways. At the discursive level, the memes demonstrate strong intertextuality with internet culture, debate culture, motivational discourse, and popular media references, allowing religious messages to circulate effectively within social media environments. At the socio-cultural level, the study identifies emerging phenomena such as horizontal preaching, digital moral surveillance, therapeutic religiosity, intellectualized faith, and digital asceticism among Indonesian Gen Z. The study concludes that religious identity among Gen Z is increasingly constructed through participatory digital culture rather than solely through formal religious institutions.